Resource use of brown trout (Salmo trutta) colour morphs in a Norwegian coastal watercourse - Grönberg, Nelli (2024)
Resource polymorphism is common in salmonid fishes and often increases diversity of the population, for instance by supporting individual variation in diet, habitat use and growth. Brown trout (Salmo trutta) can exhibit different life history traits often related to adaptation to littoral and pelagic resource use or to freshwater and marine feeding habits. Brown trout can also show variation in body colour, but the ecological basis for colour morphs, such as difference in trophic niches, remains poorly understood. Carbon, nitrogen and sulphur stable isotope analyses were conducted to investigate potential differences in long-term assimilated diets of three brown trout morphs that differed in body colour (brown, intermediate, silver). Based on the results of isotopic mixing models, the main prey items in all morphs were zooplankton and three-spined sticklebacks (Gasterosteus aculeatus). There were size related niche shifts from pelagic zooplankton diet to sticklebacks and from freshwater resources towards marine food sources in all colour morphs at the natural lengths of 250–300 mm except brown morph switched to marine food sources at the natural length of 400mm. Based on results of isotopic variation, the niche regions were overlapping among all colour morphs and silver morph had smallest niche size, however it was not significantly different. Understanding resource polymorphism within a population gives us insight to the possible harms the morphs in the population might face due to possible environmental changes.